2014
DOI: 10.5414/cp202048
|View full text |Cite
|
Sign up to set email alerts
|

Influence of St. John’s wort on the steadystate pharmacokinetics and metabolism of bosentan

Abstract: SJW increased CYP3A activity but had no consistent effect on bosentan clearance. However, inter-individual changes of the interaction were large, suggesting that close monitoring of bosentan effects may be advisable. The contribution of CYP2C9 to this interaction seems to be minor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Therefore, several controlled clinical studies have been issued proving that SJW significantly modifies the pharmacokinetics of drugs that are substrate of CYP3A, 2C9, 2C19, 2E1 or transported by P-gp or both, including midazolam [ 33 ], simvastatin [ 36 ], amitriptyline [ 37 ], chlorzoxazone [ 38 , 39 ], methadone [ 40 ], ethinyl estradiol/norethindrone combination oral contraceptives [ 41 , 42 ], fexofenadine [ 43 ], warfarin [ 44 ], imatinib [ 45 ], omeprazole [ 46 ], mephenitoin [ 47 ], tacrolimus [ 48 ], verapamil [ 49 ], voriconazole [ 50 ], talinolol [ 51 ], gliclazide [ 52 ], nifedipine [ 53 ], ketamine [ 54 ], zolpidem [ 55 ], bosentan [ 56 ], ambrisentan [ 57 ] and docetaxel [ 58 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, several controlled clinical studies have been issued proving that SJW significantly modifies the pharmacokinetics of drugs that are substrate of CYP3A, 2C9, 2C19, 2E1 or transported by P-gp or both, including midazolam [ 33 ], simvastatin [ 36 ], amitriptyline [ 37 ], chlorzoxazone [ 38 , 39 ], methadone [ 40 ], ethinyl estradiol/norethindrone combination oral contraceptives [ 41 , 42 ], fexofenadine [ 43 ], warfarin [ 44 ], imatinib [ 45 ], omeprazole [ 46 ], mephenitoin [ 47 ], tacrolimus [ 48 ], verapamil [ 49 ], voriconazole [ 50 ], talinolol [ 51 ], gliclazide [ 52 ], nifedipine [ 53 ], ketamine [ 54 ], zolpidem [ 55 ], bosentan [ 56 ], ambrisentan [ 57 ] and docetaxel [ 58 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, some data show that a treatment period of 14-days with SJW [33,34] is needed to produce significant effect on CYP3A4 activity while a short-term one doesn't induce any effect [33,35]. Therefore, several controlled clinical studies have been issued proving that SJW significantly modifies the pharmacokinetics of drugs that are substrate of CYP3A, 2C9, 2C19, 2E1 or transported by P-gp or both, including midazolam [33], simvastatin [36], amitriptyline [37], chlorzoxazone [38,39], methadone [40], ethinyl estradiol/norethindrone combination oral contraceptives [41,42], fexofenadine [43], warfarin [44], imatinib [45], omeprazole [46], mephenitoin [47], tacrolimus [48], verapamil [49], voriconazole [50], talinolol [51], gliclazide [52], nifedipine [53], ketamine [54], zolpidem [55], bosentan [56], ambrisentan [57] and docetaxel [58] (Table 1). Intriguingly, SJW interaction was expanded to multidrug resistance ATP-binding cassette (ABC) proteins and solute carrier (SLC) transporters as reported initially in a case report [59].…”
Section: St John's Wort (Sjw)mentioning
confidence: 99%
“…Search term ‘Hypericum’ resulted in 2500 references, of which 807 were published after 31 December 2009. Overall, this resulted in a total of 59 pharmacokinetic interaction studies (Table ) of which 12 were identified since 2010 . Each study investigated interactions with Hypericum products reported to have a high‐hyperforin content.…”
Section: Resultsmentioning
confidence: 99%
“…There are numerous intrinsic and extrinsic factors that can alter medication effectiveness and/or side effects among individuals. These include, but are not limited to, drug solubility [ 51 ], intestinal pH [ 51 ], drug interactions [ 52 ], age [ 53 ], sex [ 53 , 54 ], weight [ 53 ], diet [ 55 , 56 ], genetics [ 57 ], circadian rhythms [ 58 ], supplement use [ 59 ], health of the individual [ 60 ], developed tolerance [ 61 ], dosage [ 62 ], route of administration [ 62 ], etc.…”
Section: Discussionmentioning
confidence: 99%